2019
DOI: 10.1002/pld3.165
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying the enhanced biomass and abiotic stress tolerance phenotype of an Arabidopsis MIOX over‐expresser

Abstract: Myo ‐inositol oxygenase (MIOX) is the first enzyme in the inositol route to ascorbate (L‐ascorbic acid, AsA, vitamin C). We have previously shown that Arabidopsis plants constitutively expressing MIOX have elevated foliar AsA content and displayed enhanced growth rate, biomass accumulation, and increased tolerance to multiple abiotic stresses. In this work, we used a combination of transcriptomics, chromatography, microscopy, and physiological measurements to gain a deeper und… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 136 publications
1
25
0
1
Order By: Relevance
“…The expression of MIOX4 or AVP1 enhances the abiotic stress tolerance of transgenic plants. Transcriptomic studies of MIOX4 OE plants revealed that AVP1 expression is independent of MIOX4 expression (Nepal et al, 2019); therefore, we hypothesize that the co-expression of AVP1 and MIOX4 will further improve abiotic stress tolerance. Here, we use high-throughput phenotyping approaches and real-time quantitative PCR (qPCR) to characterize the additive effects of AVP1 and MIOX4 in A. thaliana exposed to water-limitation and salt stress.…”
mentioning
confidence: 88%
See 3 more Smart Citations
“…The expression of MIOX4 or AVP1 enhances the abiotic stress tolerance of transgenic plants. Transcriptomic studies of MIOX4 OE plants revealed that AVP1 expression is independent of MIOX4 expression (Nepal et al, 2019); therefore, we hypothesize that the co-expression of AVP1 and MIOX4 will further improve abiotic stress tolerance. Here, we use high-throughput phenotyping approaches and real-time quantitative PCR (qPCR) to characterize the additive effects of AVP1 and MIOX4 in A. thaliana exposed to water-limitation and salt stress.…”
mentioning
confidence: 88%
“…Seeds of the A. thaliana AVP1 OE line (AVP1-1) were provided by R.G. The A. thaliana MIOX4 OE line was developed as described by Nepal et al (2019). The seeds were surface-sterilized http://www.wileyonlinelibrary.com/journal/AppsPlantSci © 2020 Nepal et al and the AVP1 OE, MIOX4 OE, and crosses (described below) were sown on Murashige and Skoog (MS) medium (Murashige and Skoog, 1962) plus kanamycin, while the WT Col-0 controls were sown on MS medium.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that MIOX plays a role in the response to environmental stresses. In Arabidopsis, MIOX is encoded by a gene family of four members, it has been reported that Arabidopsis MIOX4 over express can increase the tolerance to cold, heat and salt [3,[6][7][8]. In addition, it has also been reported that rice MIOX has a speci c function in drought stress tolerance by decreasing oxidative damage [9].…”
Section: Introductionmentioning
confidence: 99%